Investigating sport persistence through the development of the Sport Persistence Questionnaire - Karolina Eszter Kovács; Csilla Csukonyi (Scientific Reports)
Abstract Regarding sporting activity, one of the most important indicators of effectiveness may be sport persistence, a complex concept, a terminology referring to the mastery, form, level and efficacy of sporting activity. It encompasses our attempts concerning the performance plateau, failures, injuries, or even the resolution, processing and utilisation of stressful situations associated with success and positive events, combining the physical, mental and social aspects of sport. In our study, we aimed to describe the development of a tool to measure sport persistence. Accordingly, our research involved a multi-step process. Based on the experience of a preliminary research [N = 1165], a sport persistence principal component was created including four items, which was a reliable but not nuanced variable. To provide a nuanced picture of sport persistence, a 95-item long questionnaire was developed and tested during the pre-test [N = 1105], which was revised and analysed during the post-test [N = 212]). The results of both the pre-testing and post-testing phases indicated that the 13-item Sport Persistence Questionnaire (SPQ) instrument, which scores items on a five-point Likert scale, is reliable for measuring sport persistence (Cronbach’s α = 0.943). The indicators of the model fit were also found to be adequate. The instrument measures the level of sport persistence in one dimension. In conclusion, the findings of this study may be useful concerning tailored interventions in fostering sport persistence, applicable for coaches, educators and policymakers as well. The instrument provides a sound basis for further research. In the future, the investigation of sport persistence of competitive and recreational youth athletes will be available to detect the characteristics of sport persistence, including the qualitative, quantitative and longitudinal analysis of individual, micro, meso-, exo- and macro-level factors influencing sport persistence and intervention programs supporting persistent sporting behaviour.